2013
DOI: 10.1248/yakushi.12-00242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhibitory Activity on Mycelial Growth of <i>Candida albicans</i> and Therapy for Murine Oral Candidiasis by the Combined Use of Terpinen-4-ol and a Middle-chain Fatty Acid, Capric Acid

Abstract: The combined eŠect of terpinen-4-ol, the main component of tea tree oil, and capric acid against mycelial growth of Candida albicans and murine oral candidiasis was evaluated in vitro and in vivo. Mycelial growth of C. albicans was estimated by the Cristal violet method. Combination of these compounds revealed a potent synergistic inhibition of growth. Therapeutic e‹cacy of the combination was evaluated microbiologically in murine oral candidiasis, and its application of the compounds clearly demonstrated ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…It has been reported that a combination of capric acid and terpinen-4-ol, a major component of tea tree oil, inhibits Candida hyphal growth synergistically (10). We have also reported that oligonol, a low-molecularweight polyphenol formulation derived from lychee fruit, inhibits Candida hyphal growth (11).…”
Section: Inhibition Of C Albicans Hyphal Growth By Saturated Fatty Amentioning
confidence: 88%
“…It has been reported that a combination of capric acid and terpinen-4-ol, a major component of tea tree oil, inhibits Candida hyphal growth synergistically (10). We have also reported that oligonol, a low-molecularweight polyphenol formulation derived from lychee fruit, inhibits Candida hyphal growth (11).…”
Section: Inhibition Of C Albicans Hyphal Growth By Saturated Fatty Amentioning
confidence: 88%
“…Although, the 1,8cineole is the main component of all essential oils (see Table 3 largiflorens has lowest α-pinene (2.3 %) in its oil, therefore, the α-pinene can not be considered as active antifungal compound. Therefore, a direct relationship between terpinen-4-ol content and antifungal 48 . As it is observed from Table 3, the oil of E. largiflorens contains 15.1 % of cryptone and 11.2 % of 4-allyloxyimino-2-caren, while these two compounds were not present in other oils, except for E. oleosa (containing 1.7 % of crypton).…”
Section: The Relationship Between Antifungal and Oils Constituentmentioning
confidence: 99%
“…In preceding papers, we have reported that oral treatment with tea tree oil (TTO) and its main component, terpinen-4-ol (T-4-ol), improved Candida infected lesions on the tongue's surface and lowered the number of Candida cells in the murine oral cavity. 7,12) Interestingly, although TTO and T-4-ol showed an efficacy in oral candidiasis, the recovery of lesion score and the decrease in viable Candida cell number were not correlated 7) ; that led us to assume that there might be several factors affecting the therapeutic results other than the direct anti-Candida efficacy.…”
mentioning
confidence: 96%
“…7) Experimental findings in vitro indicated that TTO and/or T-4-ol suppress hyphal growth of C. albicans at low concentrations 12,13) or possess anti-inflammatory activity. 14,15) In this study, we investigated quantitatively: 1. inflammatory responses in murine oral candidiasis, and 2. suppressive efficacy of T-4-ol against the inflammation.…”
mentioning
confidence: 99%